2014
DOI: 10.1002/2014ja020447
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ionospheric strong range spread F and scintillations observed in Vanimo station

Abstract: Data from the ionospheric scintillation monitor and ionosonde at the low-latitude station Vanimo (2.7°S, 141.3°E; dip latitude 11°S) in the Southern Hemisphere in 2003 were statistically analyzed to study the correlation between scintillations and strong range spread F (SSF). The results showed that the observed SF had four types: frequency spread F, mixed spread F, range spread F (RSF), and strong range spread F (SSF). SSF and scintillations usually occurred simultaneously and had nearly the same periods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Figure 1d gives two examples of the ionograms at 12:45 UT and 13:00 UT, showing that the range spread (diffuse echoes) started from the low-frequency part of F layer echo trace and extended beyond the f o F 2 . This kind of ESF is called strong range spread F (SSF), which has been proven its high correlation with GPS scintillation occurrence at the same station in EIA region by statistical studies (Alfonsi et al, 2013;Shi et al, 2011;Wang et al, 2014) and is identified as a manifestation of EPB. The f o F 2 at Vanimo near 20:00 LT is normally~8 MHz.…”
Section: Case 1: Observation On 1 June 2003 At Vanimomentioning
confidence: 99%
“…Figure 1d gives two examples of the ionograms at 12:45 UT and 13:00 UT, showing that the range spread (diffuse echoes) started from the low-frequency part of F layer echo trace and extended beyond the f o F 2 . This kind of ESF is called strong range spread F (SSF), which has been proven its high correlation with GPS scintillation occurrence at the same station in EIA region by statistical studies (Alfonsi et al, 2013;Shi et al, 2011;Wang et al, 2014) and is identified as a manifestation of EPB. The f o F 2 at Vanimo near 20:00 LT is normally~8 MHz.…”
Section: Case 1: Observation On 1 June 2003 At Vanimomentioning
confidence: 99%
“…We can see that the period of the blob observed was within the periods of ionospheric scintillations from the three GPS signals. All three GPS signals showed amplitude scintillations with S 4 > 0.3 which are considered as moderate or strong scintillation [Alfonsi et al, 2013;Wang et al, 2014]. The IPPs of the GPS signal of PRN 6 were the closest one to the plasma blob observed by ROCSAT-1, and the signal showed the strongest scintillation with the highest S 4 index of about 0.9.…”
Section: Analysis and Resultsmentioning
confidence: 93%
“…The scintillation index S 4 is calculated as the standard deviation of the GPS signal power amplitude normalized by its mean value at 1 min resolution [ Kil et al ., ]. The internal receiver noise has been removed, and the amplitude scintillation index is taken as S 4 > 0.3 which is considered as moderate or strong scintillation [ Alfonsi et al ., ; Wang et al ., ]. Only the data obtained above 25° elevation angle are considered, in order to reduce the impact of nonscintillation‐related tracking errors (such as multipath).…”
Section: Methodsmentioning
confidence: 99%
“…Processing of the GPS-SCINDA data was done using the GPS-TEC application software (Seemala and Valladares 2011). In this study, amplitude scintillations with S4 > 0.3 were considered as relevant scintillation events, similar to Akala et al 2011, Alfonsi et al (2013), and Wang et al (2014). Only S4 data corresponding to ray path elevations above 30° was considered to avoid the multipath effects.…”
Section: Amplitude Scintillation From Gps-scindamentioning
confidence: 99%